(untitled) (Global Journal of Medical Research, 2023)
Recent research into cancer stem cells has refined our knowledge of the origins maintenance and progression of cancer The characteristics of tumor initiating cells and the stem-like properties of tumor side populations that appear to be responsible for tumor maintenance and metastasis have given insights into potential targets for the elimination of treatment-resistant and residual tumor cells These insights have also provided inroads to understanding and preventing invasive and metastatic progression of cancer In this review we discuss recent advancements in understanding of tumor initiating cells and cancer stem cells and their implications on cancer pathobiology and treatment The role of tumor initiating cell phenotypes on routes of metastasis and the use of stemness markers to guide prognosis and treatment are also discussed Particular emphasis sections are included that focus on the role of stemness in the pathobiology and treatment of prostate cancer Of particular interest is the correlation of stemness with decreased androgen receptor expression and resistance to anti-androgen therapy The overview provided herein represents a primer for the understanding of current knowledge regarding cancer stem cells and their clinical implications in prostate and other cancer types